Enabling ICT integration in mathematics learning for the learner - Singh, Jayveer (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics, to most be complex and difficult subject in social scenario, past of the learner consider this subject as boring and burdening. Technology is an important component of all the teaching, facilitating, educating and learning processes involved in Mathematics. This is especially true if we seek ―holistic transformation of Mathematics in a digital era‖. The integration of ICT in learning mathematics and its concepts (Theorems, postulate, derivations, formulas, and ideas) has added complexity to the fundamental knowledge of mathematics. ICT create platform for assessing mathematical ideas and information through web-resource. As searching, locating, selecting, extending, and authenticating etc. enabling   ICT Integration in mathematics and other subject we can used for storage, transform, enhance, enrich, explore, research, and retrieve of the knowledge. The help of ICT-tools we enabling to transfer mathematical content and its concepts in a joyful way